Difficult Capacity Cases—The Experience of Liaison Psychiatrists. An Interview Study Across Three Jurisdictions - Kane, Nuala B.; Ruck Keene, Alex; Owen, Gareth S.; Kim, Scott Y. H. (Frontiers in Psychiatry, 2022)
Background: Assessment of capacity for treatment and discharge decisions is common in the general hospital. Liaison psychiatrists are often asked to support the treating medical or surgical team in difficult capacity assessments. However, empirical research on identification and resolution of difficult capacity cases is limited. Some studies have identified certain patient, decisional, and interpersonal factors which cause difficulty, but no study has explored how these issues are resolved in practice. Our study therefore aimed to describe how experienced liaison psychiatrists identify and resolve difficult capacity cases in a general hospital setting. Methods: We carried out semi-structured interviews with 26 liaison psychiatrists from England, Scotland, and New Zealand, on their most difficult capacity cases. Thematic analysis was used to examine types of difficulty and how these were resolved in practice. Summaries were prepared and example quotes extracted to illustrate phenomena described. Results: We identified four types of difficulty in capacity assessment, spanning both clinical and ethical domains: 1) Difficulty determining whether the decision is the patient’s own or driven by illness, 2) Difficulty in applying ethical principles, 3) Difficulty in avoiding personal bias, and 4) Procedural difficulties. The liaison psychiatrists presented as self-reflective and aware of challenges and pitfalls in hard cases. We summarised their creative strategies to resolve difficulty in assessment. Conclusion: Practitioners approaching difficult capacity cases require both clinical skills, e.g., to uncover subtle illness impairing decision-making and to consider interpersonal dynamics, and ethical skills, e.g., to negotiate the role of values and risks in capacity assessment. Education and training programmes should incorporate both aspects and could include the resolution strategies identified in our study. Practitioners, supported by health and social care systems, should work to develop self-aware and reflective capacity assessment practice.